Mediators and clinical treatment for cancer cachexia: a systematic review - Zhipeng Cao; Andrew M. Scott; Nick J. Hoogenraad; Laura D. Osellame (Wiley, 2021)
Abstract Background Cachexia, a complex multi‐organ syndrome, shortens survival time of patients, particularly those with cancer. Many studies and clinical trials have been carried out to identify cachexia‐inducing factors and potential treatments for cancer cachexia over the last 20 years. Of these factors, some are promising targets for treatment in humans, owing to their expression profiles in patients. Several clinical interventions, which act on either cachexia‐inducing factors or tissues affected by cachexia, have been developed. Some have had positive effects in the treatment of cancer cachexia; however, the question remains whether these interventions reverse cancer cachexia and could be used as standard interventions for disease treatment. The aim of this review is to understand the basic mechanisms and factors that induce cancer cachexia and their efficacies in clinical trials, providing a better outlook for future studies of cancer cachexia. Methods A systematic search was performed using PubMed and ClinicalTrials.gov databases for cachexia mediators and clinical trials. Results Of all databases and peer‐reviewed facts considered, 256 papers and 35 clinical trials were included in this systematic review. Twenty‐one mediators were identified, and 17 clinical interventions were reported in these studies. Outcomes of these clinical trials were assessed on changes in overall survival, body weight, lean body mass, appetite, muscle strength, muscle function, quality of life, and cytokine levels. Conclusions There is no current standard or successful intervention for treating cancer cachexia. Further research is needed to improve our understanding of initiators of cachexia to achieve successful outcomes in cachexia clinical trials.